Analysing Factors of Inbound Logistics and their Impact on Non-Financial Performance of Handicraft Firms - Jahangir Ahmad Bhat; Pushpender Yadav (International Journal of Supply Chain Management, 2018)
The purpose of this research paper is to explore the factors in association with inbound logistics and to analyze the relation of such attribute with the performance of handicraft firms. To identify the relationship between inbound logistics and performance, important measures are reflected in both the broader components. For inbound logistics, Market Factors(MF), Funding (FUN), and Quality Check (QC) are taken as the imperative variables while analysing performance specific aspects productivity, efficiency and flexibility are taken into reflection. Further, it is important to establish a procedure which evaluates the impact of independent variables (MF, FUN, and QC) on performance (dependent variable). The relation between the dependent and independent variable is analysed with the help of SPSS (regression analysis).